Preliminary evaluation of fecal fatty acid concentrations in cats with chronic kidney disease and correlation with indoxyl sulfate and p‐cresol sulfate. (6th November 2019) - Summers, Stacie; Quimby, Jessica M.; Phillips, Robert Kyle; Stockman, Jonathan; Isaiah, Anitha; Lidbury, Jonathan A.; Steiner, Joerg M.; Suchodolski, Jan
Abstract: Background: Straight‐ and branched‐chain (BCFA) short‐chain fatty acids (SCFAs) are produced by colonic microbiota and have both beneficial and deleterious effects in humans with chronic kidney disease (CKD). Fecal SCFAs in cats with CKD have not been described. Objective: To characterize fecal SCFA concentrations in cats with CKD as compared to healthy geriatric cats and correlate SCFA to serum indoxyl sulfate (IS) and p‐cresol sulfate (pCS) concentrations. Animals: Twenty‐eight cats with CKD (International Renal Interest Society [IRIS] stages 2, 3, and 4) and 11 older (≥ 8 years) healthy geriatric cats. Methods: Prospective, cross‐sectional study. Voided feces were analyzed using stable isotope dilution gas chromatography‐mass spectrometry to determine fecal concentrations of SCFAs. Serum concentrations of IS and pCS were measured using liquid chromatography tandem mass spectrometry. Results: Fecal isovaleric acid concentrations were significantly higher in CKD cats( P = .02) Cats with IRIS CKD stage 3 and 4 had significantly higher fecal isovaleric acid concentrations compared to healthy geriatric cats ( P = .03), but not compared to IRIS CKD stage 2 cats. Total fecal concentrations of BCFAs were found to correlate weakly with serum creatinine concentration (rho, 0.33; P = .05), blood urea nitrogen concentration (rho, 0.40; P = .01), and pCS concentration (rho, 0.35; P = .04). Conclusions and Clinical Importance: Fecal isovaleric acid concentrations were higher in CKD cats, particularly in late stage disease, compared to healthy geriatric cats. Fecal BCFA concentrations correlated with pCS and were higher in cats with muscle wasting, providing evidence for malassimilation of protein in CKD cats.